The Oxford handbook of language and sexuality - Hall, Kira; Barrett, Rusty (Oxford University Press, 2018)
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; outils; ouvrages de références; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; sociolinguistique; thématiques

Masculine stances and the linguistics of affect: on masculine ease - Kiesling, Scott F. (NORMA, 2018)
The connections between sociolinguistic conceptions of stance and the notion of affect are explored. After an explication of sociolinguistic theory, a view of stance based on three dimensions of evaluation, investment, and alignment is articulated. It is argued that low investment stances are connected to masculinity, and through that to a wider affect of ‘masculine ease.’
Keywords: approches et analyses; cours; discipline; lin2685; linguistique; masculinité; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociolinguistique; théorie des affects